Effect of Anisakis simplex (sl) larvae on the spoilage rate and shelf-life of fish mince products under laboratory conditions - Svanevik, Cecilie Smith; Lunestad, Bjørn Tore; Levsen, Arne (Food Control, 2014)
Wild caught marine fish are commonly infected with anisakid nematodes lodging in the intestinal linings or in the fish muscle. One of the most commonly found nematode parasites in marine fish is Anisakis simplex. During production of mince from the muscle of wild caught Anisakis-infected fish, the larvae would be disrupted during mince production. Any bacteria within or on the surface of such larvae are during the mincing process evenly distributed throughout the mince, and could thus possibly affect the spoilage rate of the final products. To explore if or how any bacteria associated with muscle-invading Anisakis larvae may affect the spoilage rate of fish mince, a controlled storage trial was conducted. Fillets of farmed Atlantic cod (Gadus morhua), exclusively fed on dried and heat-treated compound feed and hence expectably free from Anisakis larvae, were aseptically collected and homogenised. Fish mince aliquots were added different volumes of Anisakis homogenate based on larvae which were freshly sampled from the visceral cavity of NE Atlantic blue whiting (Micromesistius poutassou). The volumes of added parasite homogenate (parasite(+)-samples) reflected different infection intensities from 15 (low) to 50 (high) larvae per 100 g fish fillet, representing an actual Anisakis intensity range in the flesh of blue whiting. The samples were kept at 4 °C for 15 days and subjected to microbiological, sensory and chemical evaluation at 3 days intervals. Upon visual examination and plate count measurements (PC) on Iron Agar Lyngby (IAL), the samples without any parasite additives (no[parasite]) spoiled differently and more rapidly than any of the parasite(+)-samples. However, H2S-producing bacteria were only recorded in the latter samples, which were also the only ones that showed increased levels of the spoilage indicator substance trimethylamine (TMA). Moreover, the parasite(+)-samples changed their sensory characteristics at a later stage compared to the no[parasite]-samples. Although some cultures of ...